Business for the 21st century : towards simplicity and trust - Dupuy, Francois (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'Through 18 brand new case studies this book shows how companies did not manage labor and customers as long as they did not need to. With competition becoming tougher and tougher, they tried to recover control, using more and more processes and reporting systems. The result is exactly the opposite: the more they rule, the more they lose control'--
Includes bibliographical references and index.
Keywords: Industrial management -- History -- 21st century; Business enterprises -- History -- 21st century; Organizational behavior -- History -- 21st century